A literature review of benson relaxation technique for reducing anxiety in patients with chronic kidney disease - Mardiah, Adriana; Widodo, Arif; Thuy, Luu Thi (Universitas Muhammadiyah Magelang, 2022)
Hemodialysis is cleaning blood through an artificial kidney or dialyzer assisted by a machine. Kidney failure patients undergoing therapy experience anxiety due to various stressors. One way to overcome fear is to use relaxation therapy, including Benson relaxation. Benson relaxation is a breathing relaxation technique with the addition of an element of belief in the form of words that express the anxiety that the patient is experiencing. This literature aims to determine the effectiveness of Benson's relaxation on reducing stress in chronic kidney failure patients undergoing hemodialysis. A literature review comparing some literature through the journal databases used is Pubmed, Google Scholar, ScienceDirect, Garuda Portal, and Jane Semantic. The keywords are